Andreev reflection in the enhanced superconducting phase of Cu0.04PdTe2. (1st December 2022) - Vasdev, Aastha; Kumar, Ritesh; Hooda, M.K.; Yadav, C.S.; Sheet, Goutam
Abstract: A unique superconducting phase where type I and type II superconductivity coexist was seen below 1.7 K in the Dirac semimetal PdTe 2 . The mixed superconducting phase was attributed to the local variation of the Ginzburg–Landau parameter( κ ) in PdTe 2 . In such a scenario, it is imperative that introduction of disorder would make the system homogeneously type II. Here, we report our study of Point contact Andreev Reflection Spectroscopy on the 4% Cu intercalated PdTe 2 single crystals. Cu-intercalates help enhance the critical temperature by donating carriers to the system, and at the same time act as scattering centres thereby reducing the effective κ . Our detailed magnetic field dependent point contact spectroscopy studies show a typical type-II behaviour in Cu-PdTe 2 . A conventional BTK analysis of the spectra revealed a BCS-like gap Δ 0 = 330 μ eV . With 2 Δ 0 / k B T c = 4 . 25, Cu-PdTe 2 falls in the strong coupling regime. Highlights: Mixed type-I and type-II superconducting phase disappears in PdTe2 upon Cu intercalation. Homogeneous type-II superconducting phase appears in Cu0.04PdTe2. Critical temperature gets enhanced from 1.7 K to 2.5 K upon intercalation.